EKSISTENSI PATIWANGI DALAM PERKAWINAN NYEROD PASCA KEPUTUSAN MAJELIS UTAMA DESA PAKRAMAN BALI NOMOR 01/KEP/PSM-3/MDP BALI/X/2010 - Si Ngurah Ardhya (Jurnal Komunikasi Hukum, 2022)
This study aims to find out the philosophical, sociological and juridical basis for the issuance of the Decree of the Main Council of Desa Pakraman Bali Number 01/KEP/PSM-3/MDP Bali/X/2010 regarding the elimination of Patiwangi in Nyerod marriages, as well as the internalization of Patiwangi in Nyerod marriages after the issuance of the Decree Main Council of Desa Pakraman Bali Number 01/KEP/PSM-3/MDP Bali/X/2010. This research is a normative juridical research, with a statutory approach. The data used is secondary data, the legal materials used are primary and secondary legal materials. The collection of legal materials is carried out using library research. Analysis of legal materials was carried out systematically and presented in a qualitative descriptive manner. The philosophical basis for the issuance of the Decree of the Main Assembly of Desa Pakraman Bali Number 01/KEP/PSM-3/MDP Bali/X/2010 is the Vedic philosophy which is further developed on the essence of human beings as Monopluralism and Antromorphic beings. Sociologically, women who are Nyerod will have the status of Ngambang when their marriage ends due to divorce. Juridically, the prohibition of Nyerod marriage is a form of discrimination, so it contradicts Article 16 paragraph 1 and paragraph 2 of the Universal Declaration of Human Rights. Nyerod marriages can be carried out although basically it is not recommended to be held or not to be the main choice for couples who wish to marry.